Stimulation of L‐type calcium channels increases tyrosine hydroxylase and dopamine in ventral midbrain cells induced from somatic cells. (10th March 2020) - Jefri, Malvin; Bell, Scott; Peng, Huashan; Hettige, Nuwan; Maussion, Gilles; Soubannier, Vincent; Wu, Hanrong; Silveira, Heika; Theroux, Jean‐Francois; Moquin, Luc; Zhang, Xin; Aouabed, Zahia; et al.
Abstract: Making high‐quality dopamine (DA)‐producing cells for basic biological or small molecule screening studies is critical for the development of novel therapeutics for disorders of the ventral midbrain. Currently, many ventral midbrain assays have low signal‐to‐noise ratio due to low levels of cellular DA and the rate‐limiting enzyme of DA synthesis, tyrosine hydroxylase (TH), hampering discovery efforts. Using intensively characterized ventral midbrain cells derived from human skin, which demonstrate calcium pacemaking activity and classical electrophysiological properties, we show that an L‐type calcium agonist can significantly increase TH protein levels and DA content and release. Live calcium imaging suggests that it is the immediate influx of calcium occurring simultaneously in all cells that drives this effect. Genome‐wide expression profiling suggests that L‐type calcium channel stimulation has a significant effect on specific genes related to DA synthesis and affects expression of L‐type calcium receptor subunits from the CACNA1 and CACNA2D families. Together, our findings provide an advance in the ability to increase DA and TH levels to improve the accuracy of disease modeling and small molecule screening for disorders of the ventral midbrain, including Parkinson's disease. Abstract : Using intensively characterized ventral midbrain cells derived from humans, we show that an L‐type calcium agonist can significantly increase tyrosine hydroxylase protein levels and dopamine release. Genome‐wide expression profiling suggests that L‐type calcium channel stimulation has a significant effect on specific genes related to dopamine synthesis and affects expression of L‐type calcium receptor subunits from the CACNA1 and CACNA2D families.